1991
DOI: 10.1002/j.1556-6676.1991.tb01545.x
|View full text |Cite
|
Sign up to set email alerts
|

Person‐Centered Assessment

Abstract: The use of tests and assessment in person‐centered counseling is discussed. In person‐centered counseling, the most fundamental value is honoring the client as the authority on his or her own life. The extreme focus of person‐centered theory on the “self‐authority” tends to militate against the use of tests and assessment. Person‐centered counseling includes unsystematic counselor responses, such as reactions, questions, and suggestions. This increasing involvement of the counselor as a person has implications… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…A search of the research literature showed one study of humanistic counselors’ perceptions of intuition. Daigle (2010) found the concept and use of intuitive capacity resonated well with several core conditions of a person‐centered approach (see Bozarth, 1998). Participants described how intuition was facilitative of them demonstrating empathy in the therapeutic relationship, and to a lesser extent, unconditional positive regard and congruence (Daigle, 2010).…”
Section: Literature Reviewmentioning
confidence: 97%
“…A search of the research literature showed one study of humanistic counselors’ perceptions of intuition. Daigle (2010) found the concept and use of intuitive capacity resonated well with several core conditions of a person‐centered approach (see Bozarth, 1998). Participants described how intuition was facilitative of them demonstrating empathy in the therapeutic relationship, and to a lesser extent, unconditional positive regard and congruence (Daigle, 2010).…”
Section: Literature Reviewmentioning
confidence: 97%
“…Tabla 2. Las tres condiciones centrales de la hipótesis de Carl Rogers (1957) Rogers (1961) destacó la consideración positiva incondicional, entre las demás condiciones, como el agente de cambio fundamental, una priorización aceptada por otros autores (Bozarth, 1998;Freire, 2001). La exploración de emociones extrañas o desconocidas que implica la psicoterapia, clarificó, es únicamente posible si la persona se siente aceptada incondicionalmente (Rogers, 1961).…”
Section: Congruencia O Autenticidadunclassified
“…Early descriptions of what is now referred to as therapeutic psychological testing emphasized projective tests but occasionally used intelligence and cognitive tests (Aronow & Reznikoff, 1971;Bellack, Pasquarelli, & Braverman, 1949;Berg, 1985;Harrower, 1956;Luborsky, 1953;Mosak & Gushurst, 1972). These approaches emphasize empowerment through active patient involvement and allowing for an open sharing of thoughts, reactions, and interpretations (Bozarth, 1991;Harrower, 1956). An emphasis was placed on a collaborative relationship between the patient and examiner where information was imparted using understandable language, which facilitated insight, and was applicable and useful for developing treatment recommendations (Berg, 1984).…”
Section: Therapeutic Models Of Psychological Assessmentmentioning
confidence: 99%